A Unified Approach to Measuring Poverty and Inequality: Theory and Practice - Foster, James (World Bank, 2015)
A Unified Approach to Measuring Poverty and Inequality: Theory and Practice is an introduction to the theory and practice of measuring poverty and inequality, as well as a user's guide for analyzing income or consumption distribution for any standard household dataset using the World Bank's ADePT software. The approach taken here considers income standards as building blocks for basic measurement, then uses them to construct inequality and poverty measures. This unified approach provides advantages in interpreting and contrasting the measures and in understanding the way measures vary over time and space.